2022
DOI: 10.3389/fimmu.2022.874459
|View full text |Cite
|
Sign up to set email alerts
|

Acute Silica Exposure Triggers Pulmonary Inflammation Through Macrophage Pyroptosis: An Experimental Simulation

Abstract: Silica is an essential substrate of various materials, and inhaling silica induces pulmonary diseases potentially associated with macrophage pyroptosis. Utilizing silica of micro- and nano- sizes, we explored the role of macrophage pyroptosis in silica-induced pulmonary inflammation. Under the transmission electron microscopy, we found that the internalization of silica nanoparticle induced membrane rupture and increased the number of intracellular vacuoles, and both sizes of silica could suppress cell viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…It is necessary to underline those cytokines like TNF-a and IL-1b, are also highly secreted by macrophages in response to silica particles, and therefore can also participate in SiNP induced perpetuation of inflammation, in turn sustaining the increase of lymphocytes and interaction with macrophages observed. Although we did not conduct experiments to identify possible specific proteins responsible for macrophage maturation and migration to SiNPs, several studies that did so, support our findings with an added focus on viability and proliferation of macrophages when exposed to micro-and nano-silica (59) and provided evidences of macrophage secretome induction by Si NP exposure (60). We thus can speculate that both mechanisms may co-exist i.e., T-cell independent role of SiNPs and function of macrophages as APCs since we also observed phagocytosis of SiNPs by cells resembling macrophages/mature monocytes (Figure 5).…”
Section: Discussionsupporting
confidence: 63%
“…It is necessary to underline those cytokines like TNF-a and IL-1b, are also highly secreted by macrophages in response to silica particles, and therefore can also participate in SiNP induced perpetuation of inflammation, in turn sustaining the increase of lymphocytes and interaction with macrophages observed. Although we did not conduct experiments to identify possible specific proteins responsible for macrophage maturation and migration to SiNPs, several studies that did so, support our findings with an added focus on viability and proliferation of macrophages when exposed to micro-and nano-silica (59) and provided evidences of macrophage secretome induction by Si NP exposure (60). We thus can speculate that both mechanisms may co-exist i.e., T-cell independent role of SiNPs and function of macrophages as APCs since we also observed phagocytosis of SiNPs by cells resembling macrophages/mature monocytes (Figure 5).…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, pyroptosis of AMs may play an important role in silicosis. Recently, it is shown that GSDMD-dependent pyroptosis is triggered in silica-treated AMs by activating the TLR4/NLRP3/caspase-1/GSDMD pathway, which results in aggravated pulmonary inflammation and diffuses silicon nodules [ 66 , 83 ]. Blocking pyroptosis of macrophages by inhibiting the NLRP3 inflammasome or caspase-1 reduces silica-mediated pulmonary inflammation and fibrosis [ 50 , 83 ].…”
Section: Pyroptosis and Inflammation-related Respiratory Diseasesmentioning
confidence: 99%
“…The size of silica particles in the air varies, which determines their toxic effects: the smaller the particle size, the stronger the toxicity 6,7 . As evidenced by previous studies, it is found that exposure to silica particles of nano‐size causes DNA damage to human bronchial epithelial cells (Beas‐2b) much severer than that of the microsized ones 8 .…”
Section: Introductionmentioning
confidence: 92%